Diversity, disturbance and spatial structure of wetland vegetation along a lake shore: Jorka River-Lake system (Masurian Lakeland, Poland) - Kloss, Marek; Wilpiszewska, Izabela (Polish Academy of Sciences. Institute of Ecology. Publishing Office, 2002)
In 1997-1999, phytosociological studies of the riparian vegetation were conducted in the Jorka River-Lake system, Masurian Lakeland, Poland. This vegetation performs an important function as a barrier for various chemicals, counteracting lake eutrophication. In total, 26 plant communities were identified. The riparian vegetation was represented by phytocoenoses of the classes: Alnetea glutinosae, Salicetea purpureae, Querco-Fagetea, Artemisietea and Molinio-Arrhenatheretea. The littoral vegetation comprised phytocoenoses of the classes Phragmitetea and Potamogetonetea. Plant communities typically occur in the form of strips along rivers or lake shores, and on rare occasions in the form of mosaics of overlapping patches. The degree of the transformation of riparian vegetation relative to its natural state was estimated. The plant cover was disturbed by man along 80% of the shoreline length. Spatial distribution of phytocoenoses was analysed in details along 13 transects.
Strony 489-513 : ilustracje ; 27 cm
Bibliografia na stronach 510-513
Keywords: riparian vegetation; phytosociological units; spatial distribution of plant communities; man transformation of vegetation; Masurian Lakeland; Poland